Factors Impacting Hypertension Awareness among Hypertensive Population: A Quantitative Study in a Tertiary Care Hospital in Malaysia - Mohammed, Ali Haider; Hassan, Bassam Abdul Rasool; Suhaimi, Azyyati Mohd; Blebil, Ali; Dujaili, Juman; Wayyes, Abdulrasool M. (Iraqi Journal of Pharmaceutical Sciences, 2022)
There are obstacles to high levels of hypertension awareness that are embedded in gender, income and lifestyle habits which need to be addressed leading to high levels of undiagnosed and uncontrolled hypertension. This study aimed to explore the various factors which affect hypertension awareness among a hypertensive population in a tertiary care hospital. A quantitative study was conducted among hypertensive patients at a tertiary care hospital in Selangor, Malaysia. A validated and translated questionnaire was utilised as a data collection tool. Descriptive and inferential statistical analysis was done using SPSS version 25.A thousand participants (female n=621, male n= 379) were recruited, and their mean age is 48± 11.09 years old. Approximately half of respondents were not informed by their doctor that they have hypertension. More than half of respondents were unaware about the normal range of systolic and diastolic. Female gender, Chinese race, urban resident, older adults, and tertiary education level are the most significant factors that have a great influence on the level of awareness among hypertensive population. Hypertension awareness needs to be addressed from systemic point of view to solve the growing barriers to accessing correct information about the disease. Health care providers and authorities need to regulate the manner in which information on mortal diseases is presented to the public to reduce incidence of malpractice.